LASER SPECTROSCOPY : New polarisation effects in saturated absorption spectroscopy in the field of counterpropagating light waves. (1st June 2016) - Brazhnikov, D V; Novokreshchenov, V K; Ignatovich, S M; Taichenachev, A V; Yudin, V I
Abstract: The effect of a double structure of saturated absorption resonance in the field of counterpropagating light waves interacting with atomic gas is considered, which was first studied experimentally and theoretically by Vasil'ev et al. [V.V. Vasil'ev et al., J. Exp. Theor. Phys., 112, 770 (2011)]. The effect manifests itself as a new nonlinear resonance formed as a peak in the absorption spectrum of the probe wave. The resonance is observed inside a 'conventional' dip in the spectrum of saturated absorption. Previously, this effect was theoretically described only in the frameworks of the two-level atomic model, i.e., without making allowance for degeneracy of atomic energy levels with respect to the projection of the total angular momentum and for the vector nature of light. We extend the theory of the effect to the case of real atomic systems with degenerate energy levels and arbitrary polarisations of light waves. In particular, on an example of the simple transition Fg = 1 → Fe = 0 we show that polarisation parameters of light waves may significantly affect the contrast of the new effect and the possibility of observing it at all. Conclusions of the work are confirmed both analytically and bnumerically.